Boosting Studentsâ Motivation in Speaking through Blended Learning - Susanti, Elis (UICELL, 2017)
The rapid grows of internet and technology affects the teaching and learning strategy applied in a classroom activity. Nowadays, students are getting more and more interested in the implementation of internet and technology in a teaching and learning process. Due to the fact that the use of on-line learning through the internet increases studentsâ interest, this study was conducted to find out the effect of blended learning on studentsâ motivation in speaking. As it is believed that speaking is such a complex skill to be mastered by students, this study is aimed at investigating how studentsâ motivation turned out to be after one semester taught using blended learning. This is a descriptive quantitative study in which the sample consisted of 34 students of the fourth semester in English Education Study Program STKIP Muhammadiyah Kotabumi. A questionnaire was administered to the research sample in order to collect the data of studentsâ motivation. Refering to the data analysis, it was found that most of the studentsâ motivation belongs to high motivation level (52,94%), while 32,36% of the studentsâ motivation belong to medium level of motivation, and the rest (14,71%) of the students showing low motivation in speaking. The research findings reveal the fact that the use of blended learning is effective to boost studentsâ motivation in speaking class. Therefore, it is hopefully that the lecturers teaching in this class able to apply the similar strategy in which involving the classroom teaching with internet and technology in order to trigger studentsâ awareness to learn better.